Penggunaan Beberapa Metode Ekstraksi Pada Rimpang Curcuma Untuk Memperoleh Komponen Aktif Secara Kualitatif - Yurleni, Yurleni (Biospecies, 2018)
This study aims to compare several extraction methods to obtain the active component of the qualitative Curcum rhizome. The data obtained were analyzed using descriptive analysis. Curcuma rhizome used comes from 4 types of plants Curcuma xanthorriza (temulawak), Curcuma domestica (turmeric), Curcuma mango (temu mangga) and Curcuma zedoaria (temu putih). The extraction method used consisted of maseration, reflux and soxhlet method. From the research result it was found that all three extraction methods can be used (maceration, soxhletasi and reflux) to extract the curcuma rhizomes. The result of phytochemical test of metabolite secondary detectable and very strong both of atsiri and non-essential oil group is using reflux method then new method of soxhletasi and then maceration method.